The role of community and family case study (CFCS) programme on USM medical students' professional identity development : a qualitive study - Ahmad, Anisa (2016)
BACKGROUND: Since the inception of USM medical school, the Community and Family Case Study (CFCS) programme was tailored to promote professional identity development of medical students during medical training. OBJECTIVE: This study was conducted to explore medical students’ professional identity development during CFCS programme. METHODOLOGY: A qualitative design using phenomenological approach was conducted. Data were collected by focused group discussion (FGD) and document analysis. Maximal variation of purposive sampling was applied in sampling of FGD participants. FGD session was stopped once saturation was data achieved. Four FGDs (21 participants) were performed and 116 student reflection documents were analysed by thematic analysis using Atlas.ti software. Various measures were incorporated to ensure the rigour of qualitative results. RESULTS: Based on the thematic analysis, we identified that personal identity, role identity, social identity, and research identity contribute to the development of medical students PID. The findings described that students’ gained multiple skills during the CFCS programme that contribute to the development of these four professional identities. This study showed that students developed their personal identity through sharpening their leaning skills, soft skills and personal values. While students’ role identity was developed through exposure to patient care during CFCS programme. Students also describe that the CFCS programme had fostered community awareness in developing their social identity. This study also showed that students’ research identity was developed through the use of epidemiology and research methods which were applied during research activities in the CFCS programme. CONCLUSION: This study demonstrated that the USM CFCS programme provides contextual experience for promoting the development of professional identity of medical students during medical training. In addition, the USM CFCS programme is unique in developing the research skills for the students. From that notion, medical schools need to maintain and enhance the community-based medical education as an approach to promote professional identity development of their students.